Die geographischen Grundlagen der Geschichte bei Herder, Hegel und Toynbee - Schwind, Martin (ERDKUNDE, 1960)
Herder, Hegel and Toynbee have all attempted to clarify the problem of the interrelation of physical environment and civilisation. Their conclusions are very similar and can be summarized as follows: 1 Geographical facts of common effectiveness on historical development are known neither to Herder nor to Hegel nor to Toynbee. 2 The physical environment is Man’s great vis-a-vis. Herder: Environment does not force, it induces. Hegel: Nature asks Man and Man answers; Man asks Nature and Nature answers. Toynbee: The Land challenges Man to respond. Each interplay between Land and Man is unique. No laws can be established. There are merely similar developments of the category of types. Forecasts of a development are only possible with great reser vations, since the nature of Man’s reaction can never be foretold. The outcome of an encounter arises out of the encounter itself (Toynbee). 4 Every piece of the earth’s surface, inhabited or once inhabited, embodies Man’s answers to the problems posed by Nature. Where these answers have been valid ones, they document a civilisation. Every cultural landscape is composed of Nature and materialisations of human mind. 5 The attitude of Man to his land - this may also be an inherited or conquered cultural landscape -may be such that he loses his mastery over the environment or, worse still, destroys the balance of nature. Then the land takes revenge. What it has been turned into by Man becomes either obliterated or Nature answers with catastrophes like floods and soil erosion. 6 The way in which human thoughts and desires are materialised in the different landscape is an expression of the character of the inhabitants. Thus, when interpreting the cultural landscape, the geographer highly contributes to exploring cultural morphology as such.